2010
DOI: 10.1073/pnas.0912143106
|View full text |Cite
|
Sign up to set email alerts
|

Centromere-localized breaks indicate the generation of DNA damage by the mitotic spindle

Abstract: Most carcinomas present some form of chromosome instability in combination with spindle defects. Numerical instability is likely caused by spindle aberrations, but the origin of breaks and translocations remains elusive. To determine whether one mechanism can bring about both types of instability, we studied the relationship between DNA damage and spindle defects. Although lacking apparent repair defects, primary Dido mutant cells formed micronuclei containing damaged DNA. The presence of centromeres showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 44 publications
5
96
0
2
Order By: Relevance
“…The recent discovery of centromeric DNA damage in cells with spindle defects has provided evidence for a single mechanism explaining both aneuploidy and breakage. 7 Here we will discuss some recent data pointing to the mitotic spindle as the main, and possibly only, culprit in CIN.…”
Section: Are Aneuploidy and Chromosome Breakage Caused By A Cingle Mementioning
confidence: 99%
See 3 more Smart Citations
“…The recent discovery of centromeric DNA damage in cells with spindle defects has provided evidence for a single mechanism explaining both aneuploidy and breakage. 7 Here we will discuss some recent data pointing to the mitotic spindle as the main, and possibly only, culprit in CIN.…”
Section: Are Aneuploidy and Chromosome Breakage Caused By A Cingle Mementioning
confidence: 99%
“…Spectral karyotyping showed that exactly this instability of chromosome arms occurs together with aneuploidy in Dido mutant cells. 7 Genetic mapping of breakpoints in a wide range of cell lines shows a comparable arm preference, 33 and clinical samples show frequent gains and losses of whole arms. 10,11,[43][44][45] Whereas telomeric end-to-end fusion cannot fully explain this type of instability, a pericentromeric break that leaves the telomere intact agrees with the available data.…”
Section: Evidence From Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Micronuclei form from lagging whole chromosomes 14,15 or chromosome fragments 16 that are not incorporated into the main nucleus following anaphase. 17 This can occur if the centromere is either damaged 18 or missing 19 as is the case for acentric chromosome fragments. In addition, damaged chromosomes may fuse and create a dicentric chromosome 17 that becomes attached to both spindle poles.…”
Section: Introductionmentioning
confidence: 99%